Multiphysics modeling of responsive deformation of dual magnetic-pH-sensitive hydrogel - Liu, Qimin (2021)
A magneto-chemo-electro-mechanical model is developed for simulation of the swelling behavior of the dual magnetic-pH-sensitive hydrogel that is placed in an ionic solution. In this work, four physicochemical responsive mechanisms are characterized, such as the magnetization of the hydrogel, the diffusions of solvent and ions, the ionic polarization, and the nonlinear large deformation of the hydrogel. Moreover, multiple interactions are considered, including the interactions between (i) the fixed charges and the mobile ions, (ii) the polymeric networks and solvent, and (iii) the mobile ions. Furthermore, both the hydrogel and surrounding solution are covered in the computational domain, in which the Maxwell stress is included over the hydrogel-solution interface as an additional mechanical boundary. After the multiphysics model is validated via both theoretical and experimental findings in the open literature, the magnetic, electrochemical, and mechanical performances of the magnetic-pH-sensitive hydrogel are investigated in detail, and the result shows that the abrupt change in magnetic intensity occurs and the edge effect is more pronounced when approaching the hydrogel-solution interface. Furthermore, the smaller maximum magnetic field, the higher pH level, and the longer hydrogel-magnet distance contribute to the larger swelling deformation of the hydrogel. These findings may be employed to systematically design and optimize the dual magnetic-pH-sensitive hydrogel and its relevant devices.